DAMPAK PENERAPAN PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013 TERHADAP PAJAK PENGHASILAN (PT. Bank Perkreditan Rakyat Pancur Banua Khatulistiwa Sungai Pinyuh) - B51110024, JOHAN (Jurnal KIAFE, 2014)
Impact of Implementation of Government Regulation Number 46 Of 2013 Against Income Tax at PT. Bank Perkreditan Rakyat PancurBanuaKhatulistiwa Sungai Pinyuh. The purpose of this study is to investigate the application of the calculation of income tax on the BPR and the impact of government regulation number 46 of 2013 on Income Tax BPR. This research is a qualitative case study approach. Methods of collecting data through interview techniques, study documentation with how to obtain the data and literature studies. As for how the analysis is to use calculations based on Government Regulation Number 46 Of 2013 and the interview as an analytical tool. The results of this study are PT. Bank Perkreditan Rakyat PancurBanuaKhatulistiwa has not applied the Government Regulation Number 46 Of 2013. Meanwhile impact occurring is BPR paying less Income Tax than the use of the Act in general.